2008
DOI: 10.5194/angeo-26-2899-2008
|View full text |Cite
|
Sign up to set email alerts
|

On nonstationarity and rippling of the quasiperpendicular zone of the Earth bow shock: Cluster observations

Abstract: Abstract. A new method for remote sensing of the quasiperpendicular part of the bow shock surface is presented. The method is based on analysis of high frequency electric field fluctuations corresponding to Langmuir, upshifted, and downshifted oscillations in the electron foreshock. Langmuir waves usually have maximum intensity at the upstream boundary of this region. All these waves are generated by energetic electrons accelerated by quasiperpendicular zone of the shock front. Nonstationary behavior of the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Later, rippling on similar scales was found by Lowe and Burgess []; Burgess and Scholer [] using 2‐D hybrid simulations and attributed to the surface waves developing due to the instability associated with reflected ions. Observations by [ Moullard et al , ; Lobzin et al , ] confirmed the existence of this type of rippling. Large‐scale rippling with the wavelength of about 20 ion inertial lengths was found in numerical simulations by Yuan et al [].…”
Section: Introductionmentioning
confidence: 80%
“…Later, rippling on similar scales was found by Lowe and Burgess []; Burgess and Scholer [] using 2‐D hybrid simulations and attributed to the surface waves developing due to the instability associated with reflected ions. Observations by [ Moullard et al , ; Lobzin et al , ] confirmed the existence of this type of rippling. Large‐scale rippling with the wavelength of about 20 ion inertial lengths was found in numerical simulations by Yuan et al [].…”
Section: Introductionmentioning
confidence: 80%
“…Shock ripples and their importance for particle acceleration and for formation of downstream phenomena have been the subject of several works [i.e., Gedalin, 2001, Hao et al, 2016, Hietala et al, 2009, Yang et al, 2011, 2018. Rippling was observed at the Earth's bow-shock by several authors by using multi-spacecraft data from Cluster [Horbury et al, 2002, 2001, Lobzin et al, 2008, Moullard et al, 2006 and Magnetospheric Multiscale (MMS) mission [Gingell et al, 2017, Johlander et al, 2016. As for the IP shocks, several authors [i.e., Kajdič et al, 2017, Koval & Szabo, 2010, Pulupa & Bale, 2008, Russell & Alexander, 1984, Russell et al, 2000, Szabo, 2005 discussed and/or observed their non-planar structure at scales of several tens of Earth radii (R E ), but never at ion scales.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed recent simulation studies using hybrid and PIC code showed that the shock front has nonstationarity (known as self‐reformation and shock rippling) in the quasi‐perpendicular regime where the loss cone–shaped energetic ions are detected [ Lembège and Dawson , 1987; Krasnoselskikh et al , 2002; Scholer et al , 2003; Hada et al , 2003; Lowe and Burgess , 2003]. The evidence of the shock nonstationarity was also found in Cluster observations [ Horbury et al , 2001; Moullard et al , 2006; Lobzin et al , 2007, 2008]. By noting that the upstream energetic ion characteristics changed dramatically at the transition shock angle Θ t , the idea that we pursue is that the loss cone–shaped ions are produced by nonstationary structure that starts to appear above Θ t (∼75°).…”
Section: Discussionmentioning
confidence: 85%
“…Recently, the nonstationary structures began to be detected from multipoint measurements by Cluster [ Moullard et al , 2006; Lobzin et al , 2007, 2008]. The characteristics of the upstream energetic particles produced at the bow shock should strongly depend on the shock front structures.…”
Section: Discussionmentioning
confidence: 99%